2019
DOI: 10.11604/pamj.2019.33.224.19025
|View full text |Cite
|
Sign up to set email alerts
|

Modern family planning use among people living with HIV/AIDS: a facility based study in Ethiopia

Abstract: IntroductionDespite increasing efforts to address the reproductive health needs of persons living with Human Immuno-Deficiency Virus (HIV), a high unmet need for contraception exists among HIV+ women in sub-Saharan Africa. Currently, Ethiopia promotes integration of family planning (FP) services in to HIV chronic care. Yet the contraceptive prevalence rate among clients remains low. The objective of the study was to assess the role of socio-cultural factors on modern family planning use among HIV+ clients atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the current study, the majority of the study participants had a high level of awareness of safer conception (94.5%) and modern contraceptive methods (93.0%). This is almost similar to a previous study conducted in Ethiopia, in which 95.4% of study participants had awareness of modern FP methods [28]. The results also align with previous research conducted in Tanzania, which reported a high level of knowledge about contraception methods among the participants [29].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the majority of the study participants had a high level of awareness of safer conception (94.5%) and modern contraceptive methods (93.0%). This is almost similar to a previous study conducted in Ethiopia, in which 95.4% of study participants had awareness of modern FP methods [28]. The results also align with previous research conducted in Tanzania, which reported a high level of knowledge about contraception methods among the participants [29].…”
Section: Discussionsupporting
confidence: 90%
“…The unmet need for contraception remains a global public health challenge, particularly among women of childbearing age in underdeveloped regions of the world including Nigeria [32]. Previous studies [33,21,34,35,36,20] assessing unmet family planning needs among PLWHA have mostly focused on women of reproductive age. However, this present study assessed the prevalence of unmet family planning needs in both HIV-positive women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies in various regions in sub-Saharan Africa [18,19] have reported varying prevalences of unmet family planning needs among women living with HIV and a variety of associated factors indicating region-specific differences and dynamics of unmet family planning needs. HIV-positive clients who do not use contemporary family planning are more likely to experience unintended pregnancies, which increases their risk of Mother-to-childtransmission (MTCT) and unsafe abortion [20].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Ethiopia's communication research discussed the impact of socio-cultural drivers on modern family planning methods among individuals with HIV. [ 13 ] In 2018, 690,000 Ethiopians were living with HIV and 11,000 died from it. [ 14 ] Research in the endemic country focused on the importance of sexual and reproductive health to promote safe sexual practices and HIV prevention.…”
Section: Discussionmentioning
confidence: 99%